Resultados clínicos de los pacientes hipertensos y diabéticos atendidos en el programa de crónicos en dos instituciones prestadoras de servicios de salud de la Red de Salud Ladera de Cali, Colombia, durante el periodo 2023-2024. - Valencia Lugo, Sebastián; Vega León, Andrey Gerardo; Medina Muñoz, Erick David (Revista Médica de Risaralda)
This study aimed to monitor hypertensive and diabetic patients treated at two healthcare centers of the Ladera Health Network during 2023-2024. A descriptive cross-sectional observational study was conducted using a sample of 395 patient records from the chronic disease programs of the Hormiguero and Cascajal healthcare centers. Data quality was assessed, and clinical variables were recoded according to national guidelines. Univariate analysis was performed, using frequencies for qualitative variables and measures of central tendency and dispersion for quantitative ones. Among the patients, 94.2% had hypertension (HTN), 34.7% had type 2 diabetes mellitus (T2DM), and 28.9% had both conditions. Older adults (75%) and women (68.4%) predominated. A total of 34.8% of hypertensive patients and 56% of diabetic patients were not adequately controlled. Additionally, 78.7% had dyslipidemia, and 32% of those evaluated with glomerular filtration rate (GFR) had chronic kidney disease. Notably, 25.8% of patients had no record of the recommended follow-up tests for chronic disease management. The findings reveal a high burden of risk factors such as overweight, obesity, and cardiovascular history, which threaten the effectiveness of clinical management. These results underscore the need to strengthen prevention, control, and follow-up strategies in chronic care programs. Promoting an integrated and personalized approach is essential to improving health outcomes and the quality of life for this vulnerable population.